Efeitos da extens??o de marca vertical na luxuosidade percebida - Pimenta, Renato Ferreira (2015)
This study has the objective to analyze the effects of vertical brand extension strategies, down and up, in Luxuriousness Perceived in luxury brands. Six hypotheses were tested using a quantitative approach structured questionnaires and carrying three experiments involving a total of 1009 subjects. For data analysis we used Analysis of Variance technique (ANOVA). In Experiment 1, the results suggest decreased Perceived Luxuriousness vertical brand extension down relative to the parent brand and no significant difference in Luxuriousness Perceived vertical brand extension up, in relation to the parent brand. In Experiment 2, it was found that the brand extension strategy vertically down negatively affects Luxuriousness Perceived the parent tag. And in Experiment 3 it was found that consumer attitude towards vertical brand extension down is significantly lower than the Attitude toward the parent brand.